A test of the 'one‐point method' for estimating maximum carboxylation capacity from field‐measured, light‐saturated photosynthesis. Issue 3 (31st December 2015) - De Kauwe, Martin G.; Lin, Yan‐Shih; Wright, Ian J.; Medlyn, Belinda E.; Crous, Kristine Y.; Ellsworth, David S.; Maire, Vincent; Prentice, I. Colin; Atkin, Owen K.; Rogers, Alistair; Niinemets, Ülo; Serbin, Shawn P.; et al.
Summary: Simulations of photosynthesis by terrestrial biosphere models typically need a specification of the maximum carboxylation rate ( V cmax ). Estimating this parameter using A – C i curves (net photosynthesis, A, vs intercellular CO2 concentration, C i ) is laborious, which limits availability of V cmax data. However, many multispecies field datasets include net photosynthetic rate at saturating irradiance and at ambient atmospheric CO2 concentration ( A sat ) measurements, from which V cmax can be extracted using a 'one‐point method'. We used a global dataset of A – C i curves (564 species from 46 field sites, covering a range of plant functional types) to test the validity of an alternative approach to estimate V cmax from A sat via this 'one‐point method'. If leaf respiration during the day ( R day ) is known exactly, V cmax can be estimated with an r 2 value of 0.98 and a root‐mean‐squared error (RMSE) of 8.19 μmol m −2 s −1 . However, R day typically must be estimated. Estimating R day as 1.5% of V cmax, we found that V cmax could be estimated with an r 2 of 0.95 and an RMSE of 17.1 μmol m −2 s −1 . The one‐point method provides a robust means to expand current databases of field‐measured V cmax, giving new potential to improve vegetation models and quantify the environmental drivers of V cmax variation.